2007
DOI: 10.3390/medicina43040039
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of radiofrequency ablation process in liver tissue by finite element modeling and experiment

Abstract: Medicina (Kaunas) 2007; 43(4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…A good result in this area would provide the necessary information for the accurate modeling of  and k. The current lack of this information means that it necessary to assess the impact of the common mathematical functions used to model the temperature dependence of  and k in RFA. Temperature profiles obtained in the simulations are relevant and typically found in a RF ablation regime, which validates our results in other RF problems (see for example [21] and [35]). …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A good result in this area would provide the necessary information for the accurate modeling of  and k. The current lack of this information means that it necessary to assess the impact of the common mathematical functions used to model the temperature dependence of  and k in RFA. Temperature profiles obtained in the simulations are relevant and typically found in a RF ablation regime, which validates our results in other RF problems (see for example [21] and [35]). …”
Section: Discussionsupporting
confidence: 75%
“…As regards , some studies have considered a temperature-dependence based on a polynomial relation derived from NaCl solutions [21,35]. Ji and Brace [36] recently have suggested that variations in liver electrical conductivity at temperatures near 100ºC are best modeled using a sigmoid function for microwave thermal ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation of tissue is induced at temperatures between 60 °C and 100 °C and manifests as an irreversible damage to mitochondrial and cytosolic enzymes of the cells. The temperature decreases away from the active probe and is reflected by different morphological changes in the affected tissues (Barauskas et al 2007b). These changes are morphologically described as four zones: 1 -application, 2 -central, 3 -transition and 4 -reference tissue zone.…”
Section: Discussionmentioning
confidence: 99%
“…In axisymmetric formulation, the partial differential equation (PDE), which describes the infiltration process in each finite element V reads as: [1] where: p pressure presented as hydraulic head, measured in terms of height of equivalent water column [ Cauchy boundary conditions defining the flux density at infusion eyeholes;…”
Section: Mathematical Equationsmentioning
confidence: 99%
“…The infiltrating flow of the saline makes significant influence on the overall heat transfer process taking place during RFA due to certain amount of heating energy transferred into the tissue by advection, which is the transport of heat in a vector field of solution flow velocities (1). Together with the thermal conductivity of tissues, the two heat transfer mechanisms complete the full physical view of thermal processes to be taken into account in the mathematical description of RFA ex vivo experiments.…”
Section: Introductionmentioning
confidence: 99%